2022
DOI: 10.1002/ame2.12283
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of phylogenetics to understanding the evolution and epidemiology of dengue virus

Xi Yu,
Gong Cheng

Abstract: Dengue virus (DENV) is one of the most important arboviral pathogens in the tropics and subtropics, and nearly one‐third of the world's population is at risk of infection. The transmission of DENV involves a sylvatic cycle between nonhuman primates (NHP) and Aedes genus mosquitoes, and an endemic cycle between human hosts and predominantly Aedes aegypti. DENV belongs to the genus Flavivirus of the family Flaviviridae and consists of four antigenically distinct serotypes (DENV‐1‐4). Phylogenetic analyses of DEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…Understanding the phylogeny of BPIV-3 is an important basis for clarifying its evolution, sources of transmission, and molecular epidemiology, and can improve our ability to analyze and predict disease re-emergence [ 1 , 19 ]. This study found that genotype C strains of BPIV-3 had a lower genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the phylogeny of BPIV-3 is an important basis for clarifying its evolution, sources of transmission, and molecular epidemiology, and can improve our ability to analyze and predict disease re-emergence [ 1 , 19 ]. This study found that genotype C strains of BPIV-3 had a lower genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…DENV from serotypes 1, 2, and 4 has been identified as belonging to variants involved in urban and in sylvatic cycles. 37,38 Serotypes 1, 2, and 4 have been detected in sylvatic cycles involving Asian NHPs from Macaca and Presbytis genus and Aedes niveus mosquitoes. 35,39,40 In Africa, sylvatic DENV-2 detection has been achieved in Erythrocebus patas monkeys and several arboreal Aedes sp.…”
Section: Denvmentioning
confidence: 99%
“…In both cases, there is much concern about the rise of mutations in the genome of Orthoflavivirus species adapted to sylvatic cycles and momentary disappearances of epidemic strains to sylvatic environments that can re-emerge in the future after herd immunity vanishes from human populations. 37,38,47 Regarding DENV pathogenesis, there are many molecules involved in DENV entry into host cells through interaction with the envelope protein of the virus. 48 Heparan sulfate receptors are implicated in the pathogenesis of several orthoflaviviruses enhancing viral entry efficiency into host cells, 49 while C-type lectin receptors (CLR) such as mannose receptors Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN), and its homolog, DC-SIGN-related (L-SIGN), and C-type lectin domain family 5 member A (CLE5A) have been associated with DENV entry and propagation under in vitro studies, with strong correlation between polymorphisms in DC-SIGN receptors and occurrence of dengue hemorrhagic syndrome with different patterns of inheritance in different regions of the world.…”
Section: Denvmentioning
confidence: 99%
See 1 more Smart Citation
“…The cocirculation of multiple serotypes can increase the risk of serious infections due to the risk of coming into contact with more than one serotype [ 9 ]. The genetic information presented in various studies of the evolution and global spread of DENV-2 genotypes highlights the importance of performing additional research into phenotypic variations, host adaptations, and the survival of its strains, which influence the epidemiology of DENV-2 and promote its spread in endemic areas [ 9 , 10 , 11 ]. In this context, the introduction of different serotypes and their ability to persist in the environment over time may be related to the unpredictability of clinical cases of reinfection with different serotypes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%